Effects of water safety knowledge on high-risk swimming behaviours among Chinese secondary school students: a moderated mediation model - Shi, Jiaxin; Xie, Chao; Zhang, Hui (Frontiers in Psychology, 2025)
BackgroundThe dangers of drowning as a major global public health problem continue to receive international attention. Current literature lacks to describe the mechanism of action of water safety knowledge on high-risk behaviours in swimming. Therefore, the present study constructed a moderated mediation model focusing on the mediating role of sensation seeking in the relationship and the moderating role of self-efficacy.MethodsIn this study, the scale was administered to 1800 junior high school students in central China using the whole cluster sampling method on a school-by-school basis. A total of four scales were measured, which were divided into the Water Safety Knowledge Scale for assessing students’ level of water safety knowledge, the Sensation Seeking Scale for assessing students’ tendency to seek novelty and stimulation, the Self-Efficacy Scale to measure the level of students’ confidence in their own ability to swim, and the Swimming Risky Behaviours Scale to assess the level of students’ knowledge of swimming risky behaviours. Data were analyse and processed using the software AMOS 28.0 and SPSS 27.0.ResultsThe results showed that (1) there was a significant negative effect of water safety knowledge on high-risk swimming behaviour after controlling for gender, age, and grade level. (2) There was a significant negative predictive effect of water safety knowledge on sensation seeking, while the positive predictive effect of sensation seeking on swimming high-risk behaviour was equally significant. Sensation seeking mediated the relationship between water safety knowledge and high-risk swimming behaviour. (3) Swimming self-efficacy The direct predictive effect of water safety knowledge on high-risk swimming behaviour and the mediating effect of sensation seeking were both moderated by swimming self-efficacy. For subjects with lower levels of swimming self-efficacy, sensation-seeking had a significant positive predictive effect on high-risk swimming behaviour; for subjects with higher levels of swimming self-efficacy, sensation-seeking had a stronger positive predictive effect on high-risk swimming behaviour.ConclusionThis study reveals a moderated mediating mechanism whereby sensation seeking influences high-risk swimming behaviours through adolescents’ aquatic safety knowledge, offering significant insights into the complex relationship between safety knowledge and risky behaviours. Based on these findings, it is recommended that schools and relevant authorities move beyond mere knowledge dissemination in future drowning prevention education. Instead, they should develop integrated intervention programs that combine knowledge transfer with self-efficacy enhancement and impulse management training. Tailored, precision-targeted safety education should be implemented for students with different psychological traits (such as high sensation seeking). This approach will more effectively prevent adolescent drowning incidents and promote their physical and mental well-being.